2002
DOI: 10.1001/archneur.59.12.1905
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam May Be More Effective for Late-Onset Partial Epilepsy

Abstract: These results suggest that certain subpopulations may be particularly likely to respond to levetiracetam therapy. These need to be confirmed in a larger prospective trial; however, looking for specific characteristics of patients who respond to certain drugs may lead to useful guidelines for drug choices in treating epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…76.9% were responders and 40% were seizure free during the 16 weeks of the study. Another study found a better response to LEV in late-onset epilepsy (Bazil et al 2002). …”
Section: Levetiracetammentioning
confidence: 95%
See 1 more Smart Citation
“…76.9% were responders and 40% were seizure free during the 16 weeks of the study. Another study found a better response to LEV in late-onset epilepsy (Bazil et al 2002). …”
Section: Levetiracetammentioning
confidence: 95%
“…However, one study reported that patients with temporal lobe epilepsy were more likely to be improved than patients with frontal lobe epilepsy (Bazil et al 2002). In another study, patients who had failed epilepsy surgery were much more likely to respond to LEV than patients who had never been operated: 76.1% were responders and 47.6% became seizure free compared with 34.3% responder rate and 14.7% seizure free rate in patients who never had epilepsy surgery (Motamedi et al 2003).…”
Section: Levetiracetammentioning
confidence: 99%
“…Increased of seizure activity and modification of seizures patterns have been reported with other drugs, including the GABAergic drugs vigabatrin [23] and tiagabine [24] and as well as drugs that are not GABAergic such as levetiracetam [25]. Gabapentin, a drug pharmacologically related to pregabalin, has been reported to induce life-threatening myoclonic status in a patient with benign adult familial myoclonic epilepsy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Caudal involvement of basal ganglia and temporal or parietal involvement within the cortex predict seizure 16 19 . Another study done by Bazil CW et al (2002) found a better response to LEV in late-onset epilepsy 20 . Phenytoin was taken by 50% patients at the time of registration and by 28 (42.42%) patients at the time of last follow up.…”
Section: Introductionmentioning
confidence: 90%